2021
DOI: 10.46909/journalalse-2021-005
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition and Polluants Content of Some Ecological and Conventional Green Forage Sources for Dairy Cow Feed

Abstract: The quality of feed is very important in dairy milk production. The aim of the current paper was a comparative characterisation in terms of crude chemical composition, Ca and P, heavy metals (Pb, Cd, Zn, Cu), nitrates, nitrites and pesticides, for the natural meadow and green alfalfa, cultivated in ecological and conventional systems, utilised for feeding dairy cows. Sampling and analysis were performed according to established standards and working methods: drying for dry matter (DM); calcination for crude as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is necessary to understand the chemical composition of forage grasses to prepare feed rations for dairy cows. Many studies have shown that products derived from organic farming (including milk) have a much lower risk of pollution than those derived from conventional agriculture Nacu et al [1], making them safer for human consumption. Milk is a food that is recommended for daily consumption because it has a high nutritional value and is extremely nutrient-dense [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is necessary to understand the chemical composition of forage grasses to prepare feed rations for dairy cows. Many studies have shown that products derived from organic farming (including milk) have a much lower risk of pollution than those derived from conventional agriculture Nacu et al [1], making them safer for human consumption. Milk is a food that is recommended for daily consumption because it has a high nutritional value and is extremely nutrient-dense [1].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that products derived from organic farming (including milk) have a much lower risk of pollution than those derived from conventional agriculture Nacu et al [1], making them safer for human consumption. Milk is a food that is recommended for daily consumption because it has a high nutritional value and is extremely nutrient-dense [1]. Only by feeding dairy cows fodder derived from natural ecological agriculture can natural cow milk be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation